Positive electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

JP7943860B2Active Publication Date: 2026-10-30PANASONIC ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023554678
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-22
Filing Date
2022-10-17
Publication Date
2026-10-30
Estimated Expiration
2042-10-17

Smart Images

  • Figure 0007943860000002
    Figure 0007943860000002
  • Figure 0007943860000003
    Figure 0007943860000003
  • Figure 0007943860000001
    Figure 0007943860000001
Patent Text Reader

Abstract

This nonaqueous electrolyte secondary battery positive electrode according to one embodiment comprises a positive electrode mixture layer that contains, as positive electrode active materials, first lithium-containing transition metal composite oxide particles, which are non-aggregated particles having a volume-based median diameter of 2-10 μm, and second lithium-containing transition metal composite oxide particles, which are secondary particles having a volume-based median diameter of 10-30 μm and formed by the agglomeration of primary particles having an average particle diameter of 50 nm-2 μm, and that has a first layer formed on the positive electrode core material side and a second layer formed on the first layer. The first layer contains at least the first composite oxide particles, and the content of said composite oxide particles is 80% or more relative to the total mass of the positive electrode active materials contained in the first layer. The second layer contains at least the second composite oxide particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a positive electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using said positive electrode. [Background technology]

[0002] In recent years, with the increasing adoption of non-aqueous electrolyte secondary batteries in automotive and energy storage applications, there has been a growing demand for non-aqueous electrolyte secondary batteries with high capacity and excellent output characteristics. The positive electrode significantly influences battery characteristics, including battery capacity and output characteristics, and therefore, much research has been conducted on positive electrodes. For example, Patent Documents 1 to 3 disclose positive electrodes for non-aqueous electrolyte secondary batteries that use single-crystal particles of lithium-containing transition metal composite oxide and secondary particles formed by the aggregation of primary particles as the positive electrode active material. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 07-037576 [Patent Document 2] Japanese Patent Publication No. 2018-045998 [Patent Document 3] Japanese Patent Publication No. 2020-053386 [Overview of the project]

[0004] In non-aqueous electrolyte secondary batteries, a crucial challenge is to improve output characteristics while simultaneously increasing capacity by ensuring a high packing density in the positive electrode mixture layer. However, generally, increasing the packing density of the positive electrode mixture layer tends to decrease output characteristics, making it difficult to achieve both a high packing density in the positive electrode mixture layer and excellent battery output characteristics.

[0005] The purpose of this disclosure is to provide a positive electrode for a non-aqueous electrolyte secondary battery that contributes to improving the output characteristics of the battery while ensuring a high packing density of the composite layer.

[0006] The positive electrode for a non-aqueous electrolyte secondary battery according to this disclosure comprises a positive electrode core material and a positive electrode mixture layer formed on the surface of the positive electrode core material, wherein the positive electrode mixture layer contains, as a positive electrode active material, first lithium-containing transition metal composite oxide particles which are non-aggregated particles with a volume-based median diameter of 2 to 10 μm and second lithium-containing transition metal composite oxide particles which are secondary particles formed by aggregation of primary particles with an average particle size of 50 nm to 2 μm and a volume-based median diameter of 10 to 30 μm, and further comprises a first layer formed on the positive electrode core material side and a second layer formed on the first layer, wherein the first layer contains at least the first lithium-containing transition metal composite oxide particles, and the content of the first lithium-containing transition metal composite oxide particles is 80% by mass or more relative to the total mass of the positive electrode active material contained in the first layer, and the second layer contains at least the second lithium-containing transition metal composite oxide particles.

[0007] The non-aqueous electrolyte secondary battery according to this disclosure is characterized by comprising the positive electrode, the negative electrode, and the non-aqueous electrolyte.

[0008] The positive electrode for a non-aqueous electrolyte secondary battery according to this disclosure can improve the output characteristics of the battery while ensuring a high packing density of the composite layer. [Brief explanation of the drawing]

[0009] [Figure 1] This is a cross-sectional view of a non-aqueous electrolyte secondary battery, which is an example of an embodiment. [Figure 2] This is a cross-sectional view of a positive electrode, which is an example of an embodiment. [Modes for carrying out the invention]

[0010] As described above, achieving both a high packing density in the positive electrode mixture layer and excellent output characteristics is a crucial challenge in non-aqueous electrolyte secondary batteries. The inventors of this invention have diligently studied to solve this problem and have found that by using specific non-aggregated particles and specific secondary particles in combination as the positive electrode active material, and by including a large amount of non-aggregated particles in the first layer (lower layer) formed on the core material side of the positive electrode mixture layer, the output characteristics of the battery can be effectively improved while ensuring a high packing density in the mixture layer.

[0011] Furthermore, when only non-aggregated particles are used as the positive electrode active material, the output characteristics improve, but the battery capacity decreases due to a reduction in the packing density of the positive electrode active material. On the other hand, when only secondary particles are used, particle cracking is likely to occur during the compression process of the positive electrode, and the gaps between particles become blocked by the cracked particles. Although the packing density of the active material increases, the output characteristics decrease compared to when only non-aggregated particles are used as the positive electrode active material. Moreover, when a mixture of non-aggregated particles and secondary particles is used as the positive electrode active material, it is not possible to achieve both of these characteristics simultaneously.

[0012] Hereinafter, with reference to the drawings, an example of an embodiment of the positive electrode for a non-aqueous electrolyte secondary battery according to this disclosure, and an example of an embodiment of a non-aqueous electrolyte secondary battery using said positive electrode will be described in detail. It should be noted that selective combination of the multiple embodiments and modifications described below is included in this disclosure.

[0013] In the following, a cylindrical battery in which a wound electrode body 14 is housed in a bottomed cylindrical outer casing 16 is given as an example. However, the battery casing is not limited to a cylindrical outer casing, and may be, for example, a rectangular outer casing (rectangular battery) or an outer casing made of a laminate sheet including a metal layer and a resin layer (laminated battery). Furthermore, the electrode body may be a laminated electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators in between.

[0014] Figure 1 is a schematic diagram showing a cross-section of a non-aqueous electrolyte secondary battery 10, which is an example of an embodiment. As shown in Figure 1, the non-aqueous electrolyte secondary battery 10 comprises a wound electrode body 14, a non-aqueous electrolyte, and an outer casing 16 that houses the electrode body 14 and the non-aqueous electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape via the separator 13. The outer casing 16 is a bottomed cylindrical metal container with one side open in the axial direction, and the opening of the outer casing 16 is sealed by a sealing body 17. In the following, for convenience of explanation, the side of the battery with the sealing body 17 will be referred to as the top, and the bottom side of the outer casing 16 as the bottom.

[0015] Non-aqueous electrolytes comprise a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and mixtures of two or more of these. Non-aqueous solvents may also contain halogen-substituted solvents, in which at least some of the hydrogen atoms of the solvent are replaced with halogen atoms such as fluorine. Examples of non-aqueous solvents include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and mixtures thereof. Examples of electrolyte salts include lithium salts such as LiPF6. Non-aqueous electrolytes are not limited to liquid electrolytes and may also be solid electrolytes.

[0016] The positive electrode 11, negative electrode 12, and separator 13 constituting the electrode body 14 are all elongated strip-shaped bodies that are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger in dimensions than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer in the longitudinal direction and the width direction (short direction) than the positive electrode 11. The separator 13 is formed to be at least slightly larger in dimensions than the positive electrode 11, and two separators are arranged so as to sandwich the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0017] Insulating plates 18 and 19 are arranged above and below the electrode assembly 14, respectively. In the example shown in FIG. 1, the positive electrode lead 20 extends through the through-hole of the insulating plate 18 toward the sealing body 17, and the negative electrode lead 21 extends through the outside of the insulating plate 19 toward the bottom side of the outer can 16. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the cap 27, which is the top plate of the sealing body 17 electrically connected to the internal terminal plate 23, serves as the positive electrode terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as the negative electrode terminal.

[0018] As described above, the outer can 16 is a bottomed cylindrical metal container with one axial side open. A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the internal tightness of the battery and the insulation between the outer can 16 and the sealing body 17. The outer can 16 is formed with a grooved portion 22 that supports the sealing body 17, with a part of the side surface protruding inward. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the upper portion of the outer can 16 by the grooved portion 22 and the open end of the outer can 16 that is crimped against the sealing body 17.

[0019] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve element 24, an insulating member 25, an upper valve element 26, and a cap 27 are stacked in order from the electrode assembly 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve element 24 and the upper valve element 26 are connected at their respective central portions, and the insulating member 25 is interposed between their respective peripheral portions. When an abnormality occurs in the battery and the internal pressure rises, the lower valve element 24 deforms so as to push the upper valve element 26 toward the cap 27 and breaks, thereby interrupting the current path between the lower valve element 24 and the upper valve element 26. When the internal pressure further rises, the upper valve element 26 breaks, and gas is discharged from the opening of the cap 27.

[0020] Hereinafter, the positive electrode 11, the negative electrode 12, and the separator 13, particularly the positive electrode 11, will be described in detail.

[0021] [Positive Electrode] Figure 2 is a cross-sectional view of the positive electrode 11. As shown in Figure 2, the positive electrode 11 comprises a positive electrode core material 30 and a positive electrode mixture layer 31 formed on the surface of the positive electrode core material 30. The positive electrode core material 30 can be a foil of a metal that is stable in the potential range of the positive electrode 11, such as aluminum or an aluminum alloy, or a film on which the metal is arranged on the surface. An example of the positive electrode core material 30 is an aluminum or aluminum alloy foil with a thickness of 10 to 20 μm. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably formed on both sides of the positive electrode core material 30.

[0022] Examples of conductive agents included in the positive electrode mixture layer 31 include carbon materials such as carbon black, acetylene black, Ketjenblack, graphite, carbon nanotubes, carbon nanofibers, and graphene. The content of the conductive agent is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, per 100 parts by mass of positive electrode active material.

[0023] Examples of binders included in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may also be used in combination with carboxymethylcellulose (CMC) or its salts, polyethylene oxide (PEO), etc. The binder content is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, per 100 parts by mass of positive electrode active material.

[0024] The positive electrode mixture layer 31 contains particulate lithium-containing transition metal composite oxide as the positive electrode active material. The lithium-containing transition metal composite oxide is a composite oxide containing Co, Mn, Ni, Al, etc., in addition to Li. The metal elements constituting the lithium-containing transition metal composite oxide are at least one selected from, for example, Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among these, it is preferable to contain at least one selected from Co, Ni, and Mn. Examples of suitable composite oxides include composite oxides containing Ni, Co, and Mn, and composite oxides containing Ni, Co, and Al.

[0025] The positive electrode mixture layer 31 contains two types of lithium-containing transition metal composite oxide particles with different particle shapes as positive electrode active material, and has a first layer 31a formed on the positive electrode core material 30 side and a second layer 31b formed on the first layer 31a. To the extent that it does not impair the purpose of this disclosure, the positive electrode mixture layer 31 may include a third layer, but it is preferable that the positive electrode mixture layer 31 has a two-layer structure including a first layer 31a which is a lower layer directly formed on the positive electrode core material 30 and a second layer 31b which is directly formed on the first layer 31a. The first layer 31a and the second layer 31b each contain the two types of lithium-containing transition metal composite oxide particles, or contain the two types of composite oxide particles, with different mixing ratios in each layer.

[0026] The thickness of the positive electrode mixture layer 31 is, for example, 50 to 150 μm on one side of the positive electrode core material 30. The thickness of the first layer 31a may be greater than the thickness of the second layer 31b, but is preferably less than or equal to the thickness of the second layer 31b. Since it is not easy to accurately determine the thickness ratio of the first layer 31a to the second layer 31b, the proportion of each layer in the positive electrode mixture layer 31 is evaluated by mass ratio. The second layer 31b covers the entire area of ​​the first layer 31a, and the area of ​​each layer on the positive electrode core material 30 is substantially the same. The proportion of the first layer 31a in the positive electrode mixture layer 31 is preferably 50% by mass or less.

[0027] The positive electrode composite layer 31 contains, as two types of lithium-containing transition metal composite oxide particles, first lithium-containing transition metal composite oxide particles (first composite oxide particles) which are non-aggregated particles, and second lithium-containing transition metal composite oxide particles (second composite oxide particles) which are secondary particles formed by the aggregation of primary particles with an average particle size of 50 nm to 2 μm. The first layer 31a contains at least the first composite oxide particles, and the second layer 31b contains at least the second composite oxide particles.

[0028] The positive electrode mixture layer 31 may contain only the first and second composite oxide particles as the positive electrode active material, or it may contain a third lithium-containing transition metal composite oxide particle to the extent that it does not impair the purpose of this disclosure. An example of the third lithium-containing transition metal composite oxide particle is a composite oxide particle that does not satisfy the particle size conditions described later. The content of the positive electrode active material is, for example, 90% by mass or more of the total mass of the positive electrode mixture layer 31, and may be the same or different for the first layer 31a and the second layer 31b.

[0029] The type and content of the conductive agent and binder in the positive electrode mixture layer 31 may be the same or different for the first layer 31a and the second layer 31b. In this embodiment, the same type of conductive agent is used in the first layer 31a and the second layer 31b, and the content of the conductive agent is substantially the same. Also, the same type of binder is used in the first layer 31a and the second layer 31b, and the content of the binder is substantially the same.

[0030] The volume-based median diameter (hereinafter sometimes referred to as "D50") of the first composite oxide particles is 2 to 10 μm, preferably 3 to 8 μm. The D50 of the second composite oxide particles is 10 to 30 μm, preferably 12 to 20 μm. D50 refers to the particle size at which the cumulative frequency of the smallest particle size accounts for 50% in the volume-based particle size distribution. The particle size distribution of the composite oxide particles can be measured using a laser diffraction particle size distribution analyzer (e.g., Microtrac-Bell Co., Ltd., MT3000II) with water as the dispersion medium.

[0031] The first composite oxide particle is a particle that does not have grain boundaries inside, for example, a primary particle of a single crystal. The crystallinity of the composite oxide particle can be confirmed using a scanning ion microscope. The first composite oxide particle, which is a non-aggregated particle, may contain five or fewer primary particles. In this specification, a non-aggregated particle means a particle composed of one primary particle that does not have grain boundaries inside, and a particle composed of five or fewer primary particles.

[0032] The second composite oxide particles are secondary particles formed by the aggregation of numerous primary particles with an average particle size of 50 nm to 2 μm, preferably 500 nm to 2 μm. The second composite oxide particles have numerous grain boundaries of primary particles. The primary particles can be identified by observing the second composite oxide particles with a scanning electron microscope (SEM). The multiple primary particles are firmly attached to each other, so as not to break apart even when strong forces are applied, such as during the grinding of the second composite oxide particles after synthesis or during the preparation of the cathode mixture slurry.

[0033] The average particle size of the primary particles constituting the second composite oxide particle can be determined by analyzing SEM images of the particle cross-section. For example, the positive electrode 11 is embedded in resin, a cross-section is prepared by cross-section polishing (CP), and this cross-section is photographed with an SEM. From the SEM image, 30 primary particles are randomly selected and their grain boundaries are observed. The diameter of the circumscribed circle of each of the 30 primary particles is determined, and the average value of these diameters is taken as the average particle size.

[0034] Each lithium-containing transition metal composite oxide particle can be synthesized by the method described in the examples below. The first composite oxide particle can be synthesized, for example, by increasing the pH of the alkaline aqueous solution used when synthesizing the precursor (metal composite hydroxide) containing Ni, Co, Mn, Al, etc., compared to when synthesizing the second composite oxide particle. Alternatively, it can be synthesized by increasing the calcination temperature of the precursor instead of, or in addition to, increasing the pH of the alkaline aqueous solution.

[0035] A preferred example of the pH of the alkaline aqueous solution when synthesizing the first composite oxide particles is 10 to 11, and a preferred example of the calcination temperature is 950 to 1100°C. When synthesizing the second composite oxide particles, for example, an alkaline aqueous solution with a pH of 9 to 10 is used, and the calcination temperature is set to 950°C or lower.

[0036] Each lithium-containing transition metal composite oxide particle is composed of, for example, a composite oxide having a hexagonal crystal structure belonging to space group R-3m, and is preferably LiNi x Co y Mn z O2 (0.3<x<0.6, x+y+z=1), or LiNi x Co y Al z O2 (0.8<x<0.95, x+y+z=1) as a main component. Here, the main component means the component with the largest mass among the components constituting the composite oxide particles. The composition of each composite oxide particle may be the same as or different from each other.

[0037] As described above, the positive electrode mixture layer 31 has a two-layer structure including the first layer 31a containing at least the first composite oxide particles and the second layer 31b containing at least the second composite oxide particles. The content of the first composite oxide particles in the first layer 31a is 80 mass% or more relative to the total mass of the positive electrode active material contained in the first layer 31a, and may be substantially 100 mass%.

[0038] The first composite oxide particles which are non-aggregated particles are less prone to particle cracking during the manufacturing process of the positive electrode 11, compared with the second composite oxide particles which are secondary particles. Therefore, the first composite oxide particles bite into the positive electrode core material 30, and the contact area between the positive electrode core material 30 and the positive electrode mixture layer 31 increases. Accordingly, by allowing 80 mass% or more of the first composite oxide particles to be present in the first layer 31a which is the lower layer of the positive electrode mixture layer 31, the electrical resistance between the positive electrode core material 30 and the positive electrode mixture layer 31 is reduced, and as a result, the output characteristics of the battery are considered to be improved.

[0039] The first layer 31a may contain a second composite oxide particle as a positive electrode active material. However, its content must be 20% by mass or less of the total mass of the positive electrode active material contained in the first layer 31a. If the proportion of the first composite oxide particle in the positive electrode active material of the first layer 31a falls below 80% by mass, the effect of reducing electrical resistance between the positive electrode core material 30 and the positive electrode mixture layer 31 cannot be obtained, and the output characteristics cannot be improved.

[0040] The proportion of the first layer 31a in the positive electrode mixture layer 31 is preferably 5% by mass or more, and more preferably 10% by mass or more, relative to the total mass of the positive electrode mixture layer 31. By setting the proportion of the first layer to 5% by mass or more, or 10% by mass or more, the electrical resistance between the positive electrode core material 30 and the positive electrode mixture layer 31 is effectively reduced, improving the output characteristics of the battery. There is no particular upper limit to the proportion of the first layer 31a, but from the viewpoint of increasing capacity, 50% by mass relative to the total mass of the positive electrode mixture layer 31 is preferred.

[0041] The preferred proportion of the first layer 31a in the positive electrode mixture layer 31 is 5 to 50% by mass, and more preferably 10 to 50% by mass. That is, the mass ratio of the first layer 31a to the second layer 31b is preferably 10:90 to 50:50. If the mass ratio of the first layer 31a to the second layer 31b is within this range, it becomes easier to achieve both a high packing density of the positive electrode mixture layer 31 and excellent output characteristics of the battery.

[0042] The second layer 31b may contain first composite oxide particles as a positive electrode active material. However, the content is preferably 50% by mass or less relative to the total mass of the positive electrode active material contained in the second layer 31b. The content of second composite oxide particles in the second layer 31b is preferably 50% by mass or more relative to the total mass of the positive electrode active material contained in the second layer 31b. That is, the mass ratio of first composite oxide particles to second composite oxide particles in the second layer 31b is preferably 50:50 to 0:100. The content of second composite oxide particles in the second layer 31b may be 80% by mass or more, and may be substantially 100% by mass. By adding a large amount of second composite oxide particles to the second layer 31b, the packing density of the positive electrode mixture layer 31 is increased, and the battery capacity can be increased.

[0043] The positive electrode 11 can be manufactured by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder onto a positive electrode core material 30, drying the coating, and then compressing it to form a positive electrode mixture layer 31 on both sides of the positive electrode core material 30. For example, two types of slurries with different types of positive electrode active materials can be used for the positive electrode mixture slurry. A first positive electrode mixture slurry containing only the first composite oxide particles as the positive electrode active material is applied onto the positive electrode core material 30, and then a second positive electrode mixture slurry containing only the second composite oxide particles as the positive electrode active material is applied onto the coating to form a two-layer positive electrode mixture layer 31 including a first layer 31a and a second layer 31b.

[0044] [Negative electrode] The negative electrode 12 comprises a negative electrode core material and a negative electrode mixture layer formed on the surface of the negative electrode core material. The negative electrode core material can be a foil of a metal that is stable in the potential range of the negative electrode 12, such as copper or a copper alloy, or a film on which the metal is arranged on the surface. An example of a negative electrode core material is a copper or copper alloy foil with a thickness of 5 to 15 μm. The negative electrode mixture layer contains a negative electrode active material and a binder, and is preferably formed on both sides of the negative electrode core material. The thickness of the negative electrode mixture layer is, for example, 30 to 150 μm on one side of the negative electrode core material. The negative electrode 12 can be manufactured by applying a negative electrode mixture slurry containing a negative electrode active material, a binder, etc., onto the negative electrode core material, drying the coating film, and then compressing it to form the negative electrode mixture layer on both sides of the negative electrode core material.

[0045] The negative electrode mixture layer contains, for example, a carbon-based active material that reversibly intercepts and releases lithium ions as the negative electrode active material. Suitable carbon-based active materials include natural graphite such as flake graphite, lumpy graphite, and clay-like graphite, as well as artificial graphite such as lumpy artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, a Si-based active material composed of at least one of Si and a Si-containing compound may be used as the negative electrode active material, and carbon-based active materials and Si-based active materials may be used in combination.

[0046] The binder included in the negative electrode mixture layer can be a fluororesin such as PTFE or PVdF, PAN, polyimide, acrylic resin, polyolefin, or styrene-butadiene rubber (SBR). The negative electrode mixture layer may also contain CMC or its salt, polyacrylic acid (PAA) or its salt, or polyvinyl alcohol (PVA). The binder content is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, per 100 parts by mass of the negative electrode active material. Conductive agents such as carbon black, acetylene black, or Ketjenblack may also be added to the negative electrode mixture layer.

[0047] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of porous sheets include microporous thin films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator include polyethylene, polyolefins such as polypropylene, and cellulose. The separator 13 may have a single-layer structure or a multi-layer structure. Furthermore, a highly heat-resistant resin layer, such as aramid resin, may be formed on the surface of the separator 13.

[0048] At the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12, a filler layer containing an inorganic filler may be formed. Examples of the inorganic filler include oxides, phosphate compounds and the like containing metal elements such as Ti, Al, Si, and Mg. The filler layer can be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13. [Examples]

[0049] Hereinafter, the present disclosure will be described in further detail by way of Examples, but the present disclosure is not limited to these Examples.

[0050] <Example 1> [Synthesis of non-aggregated particles (first lithium-containing transition metal composite oxide particles)] Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed at a predetermined ratio, and uniformly mixed in an alkaline aqueous solution at pH 10 to 11 to synthesize a precursor. Next, the precursor and lithium carbonate were mixed, and after firing at a temperature of 1000°C for 15 hours or more, the fired product was pulverized to obtain first lithium-containing transition metal composite oxide particles which are non-aggregated particles. The composition and particle size of the particles are as follows. Composition: LiNi 0.5 Co 0.2 Mn 0.3 O2 D50: 4.5μm

[0051] [Synthesis of secondary particles (second lithium-containing transition metal composite oxide particles)] Secondary particles (second lithium-containing transition metal composite oxide particles) formed by agglomeration of a large number of primary particles were obtained in the same manner as in the case of the first lithium-containing transition metal composite oxide particles, except that the pH of the alkaline aqueous solution was changed to 9 to 10 and the firing temperature was changed to 900°C. The composition and particle size of the particles are as follows. Composition: LiNi 0.5 Co 0.2 Mn 0.3 O2 Average particle size of primary particles: 1.6μm D50 of secondary particles: 14.1μm

[0052] [Fabrication of the positive electrode] A first mixture slurry with a solid content of 70% by mass was prepared by mixing a first lithium-containing transition metal composite oxide, which is a non-aggregated particle, acetylene black (AB), and polyvinylidene fluoride (PVdF) with an average molecular weight of approximately 1.1 million, in N-methyl-2-pyrrolidone (NMP) in a mass ratio of 98:1:1. A second mixture slurry was prepared in the same manner as the first mixture slurry, except that a second lithium-containing transition metal composite oxide, which is a secondary particle, was used instead of the first lithium-containing transition metal composite oxide.

[0053] A first mixture slurry was applied to both sides of a positive electrode core made of aluminum foil. Subsequently, a second mixture slurry was applied onto the coating of the first mixture slurry. After drying and compressing the coating (linear pressure 3000 N / m), the material was cut to a predetermined electrode size. This created a positive electrode in which a two-layer positive electrode mixture layer, consisting of a lower layer (first layer) and an upper layer (second layer), was formed on both sides of the positive electrode core. Each mixture slurry was applied so that the mass ratio of the lower layer to the upper layer was 1:1.

[0054] [Fabrication of the negative electrode] A mixture of 95 parts by mass of graphite and 5 parts by mass of silicon dioxide (SiO) was used as the negative electrode active material. A negative electrode slurry was prepared by mixing 100 parts by mass of the negative electrode active material with 1 part by mass of carboxymethylcellulose (CMC) and water, and then mixing in 1.2 parts by mass of styrene-butadiene rubber (SBR) dispersion by solid content. Next, the negative electrode slurry was applied to both sides of a negative electrode core made of copper foil, the coating was dried and compressed, and then cut to a predetermined electrode size to produce a negative electrode in which negative electrode slurry layers were formed on both sides of the negative electrode core.

[0055] [Preparation of non-aqueous electrolyte solution] Ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:3 (at 25°C). 5 parts by mass of vinylene carbonate (VC) were added to 100 parts by mass of the mixed solvent, and LiPF6 was dissolved to a concentration of 1 mol / L to prepare a non-aqueous electrolyte.

[0056] [Battery construction] Lead terminals were attached to the positive and negative electrodes, respectively, and a wound electrode body was fabricated by spirally winding the positive and negative electrodes with a separator in between. This electrode body was housed in a bottomed cylindrical outer casing, the negative electrode lead was welded to the inner surface of the bottom of the outer casing, and the positive electrode lead was welded to the internal terminal plate of the sealing body. Subsequently, the non-aqueous electrolyte was poured into the outer casing, and the opening edge of the outer casing was crimped and fixed to the sealing body to fabricate a non-aqueous electrolyte secondary battery with a battery capacity of 2500mAh.

[0057] <Example 2> In preparing the positive electrode, the amount of each mixture slurry applied was changed so that the mass ratio of the upper layer to the lower layer was 90:10, but otherwise the positive electrode and non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1.

[0058] <Comparative Example 1> In preparing the positive electrode, the positive electrode and non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1, except that the second mixture slurry was applied to the positive electrode core material before applying the first mixture slurry.

[0059] <Comparative Example 2> In preparing the positive electrode, the positive electrode and non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 2, except that the second mixture slurry was applied to the positive electrode core material before applying the first mixture slurry.

[0060] <Comparative Example 3> A positive electrode and a non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1, except that the positive electrode mixture layer was formed using only the second mixture slurry in the preparation of the positive electrode.

[0061] <Comparative Example 4> A positive electrode and a non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1, except that the positive electrode mixture layer was formed using only the first mixture slurry in the preparation of the positive electrode.

[0062] <Comparative Example 5> A mixture of non-aggregated particles (first lithium-containing transition metal composite oxide particles) and secondary particles (second lithium-containing transition metal composite oxide particles) in a 1:1 mass ratio was mixed with AB and PVdF in a 98:1:1 mass ratio. An appropriate amount of NMP was added as a dispersion medium to prepare a positive electrode mixture slurry with a solid content of 70% by mass. A positive electrode and a non-aqueous electrolyte secondary battery were prepared in the same manner as in Example 1, except that the positive electrode mixture layer was formed using only this positive electrode mixture slurry.

[0063] The performance of each positive electrode and each battery in the examples and comparative examples was evaluated using the method described below. The evaluation results are shown in Table 1.

[0064] [Packing density of the positive electrode mixture layer] The packing density of the positive electrode mixture layer was calculated by measuring the thickness and mass of the positive electrode.

[0065] [Output Characteristics] The output characteristics of the battery were evaluated using DC resistance (DCR). After initial charging and discharging, the battery was charged with a constant current of 0.2It until the battery voltage reached 4.2V. Then, it was charged with a constant voltage until the current reached 0.05It at 4.2V. After that, it was discharged for 10 seconds at a current of 1.0It, and the voltage drop due to discharge was measured. The DCR was then calculated using the following formula. DCR(mΩ) = (Voltage drop (mV) / Current value (A))

[0066] [Table 1]

[0067] As shown in Table 1, all of the batteries in the examples have lower DCR and superior output characteristics compared to the batteries in the comparative examples. In addition, the positive electrodes of the examples have a high packing density in the composite layer. From the examples and comparative examples 1 to 3, it can be understood that using the first composite oxide particles, which are non-aggregated particles, in the lower positive electrode active material reduces the DCR of the battery. Since non-aggregated particles are less prone to particle cracking during the compression process of the positive electrode, it is thought that by adding non-aggregated particles to the lower layer, the non-aggregated particles penetrate the core material, reducing the electrical resistance between the composite layer and the core material, resulting in a lower DCR.

[0068] Furthermore, from the examples and comparative examples 2-4, it can be understood that using a second composite oxide particle, which is a secondary particle, as the positive electrode active material increases the packing density of the composite layer. Since secondary particles are prone to particle cracking during the positive electrode compression process, it is presumed that when secondary particles are used, the gaps between particles are filled by the cracked particles, thereby increasing the packing density. In other words, if secondary particles are not used, the packing density of the composite layer decreases, making it impossible to increase the battery capacity. It should be noted that from comparative example 4, when the packing density decreases, there is a tendency for the DCR to increase even when non-aggregated particles are added to the lower layer.

[0069] Furthermore, from Example 2, it is understood that good power characteristics can be ensured if the mass ratio of the lower layer (lower layer containing non-aggregated particles) to the total mass of the mixture layer is 10% or more. From Example 1 and Comparative Example 5, when a single-layer mixture layer is formed by simply mixing non-aggregated particles and secondary particles, a high packing density is obtained, but the power characteristics are greatly reduced. In this case, it is presumed that the DCR increased as a result of not being able to sufficiently reduce the electrical resistance between the mixture layer and the core material compared to the example. [Explanation of Symbols]

[0070] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer casing, 17 Sealing body, 18,19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Grooved section, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating material, 26 Upper valve body, 27 Cap, 28 Gasket, 30 Positive electrode core material, 31 Positive electrode mixture layer, 31a First layer, 31b Second layer

Claims

1. A positive electrode for a non-aqueous electrolyte secondary battery comprising a positive electrode core material and a positive electrode mixture layer formed on the surface of the positive electrode core material, The positive electrode composite layer contains, as a positive electrode active material, first lithium-containing transition metal composite oxide particles which are non-aggregated particles with a volume-based median diameter of 2 to 10 μm, and second lithium-containing transition metal composite oxide particles which are secondary particles formed by aggregation of primary particles with an average particle size of 50 nm to 2 μm and a volume-based median diameter of 10 to 30 μm, and has a first layer formed on the positive electrode core material side and a second layer formed on the first layer. The first layer contains at least the first lithium-containing transition metal composite oxide particles, and the content of the first lithium-containing transition metal composite oxide particles is 80% by mass or more relative to the total mass of the positive electrode active material contained in the first layer. The second layer contains at least the second lithium-containing transition metal composite oxide particles, The mass ratio of the first lithium-containing transition metal composite oxide particles to the second lithium-containing transition metal composite oxide particles in the second layer is 50:50 to 0:

100. A positive electrode for a non-aqueous electrolyte secondary battery, wherein the proportion of the first layer in the positive electrode mixture layer is 5 to 10% by mass.

2. A positive electrode for a non-aqueous electrolyte secondary battery comprising a positive electrode core material and a positive electrode mixture layer formed on the surface of the positive electrode core material, The positive electrode composite layer contains, as a positive electrode active material, first lithium-containing transition metal composite oxide particles which are non-aggregated particles with a volume-based median diameter of 2 to 10 μm, and second lithium-containing transition metal composite oxide particles which are secondary particles formed by aggregation of primary particles with an average particle size of 50 nm to 2 μm and a volume-based median diameter of 10 to 30 μm, and has a first layer formed on the positive electrode core material side and a second layer formed on the first layer. The first layer contains only the first lithium-containing transition metal composite oxide particles as the positive electrode active material. The second layer contains only the second lithium-containing transition metal composite oxide particles as the positive electrode active material. A positive electrode for a non-aqueous electrolyte secondary battery, wherein the proportion of the first layer in the positive electrode mixture layer is 10 to 50% by mass (excluding 50% by mass).

3. The positive electrode according to claim 1 or 2, The negative electrode and, Non-aqueous electrolytes, A secondary battery equipped with [a specific feature / feature].

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and manufacture of its positive pole active material

    JP1995037576A

  • Spherical or pseudo-spherical positive electrode material of lithium ion battery, and manufacturing method and application thereof

    JP2018045998A

  • Positive electrode active material for secondary battery and method of producing the same

    JP2020053386A

  • Nonaqueous electrolyte secondary battery

    JP2022112207A

  • Nonaqueous electrolyte secondary battery

    WO2018150843A1